Kisses [videorecording (DVD)] - Daly, Lance; O'Neill, Kelly; Curry, Shane; Roe, Paul; Conroy, Neilí (Oscilloscope Laboratories, 2010)
After being abused by their dysfunctional families, pre-teen neighbors Dylan and Kylie decide to run away from home on Christmas Eve. The two set off in search of Dylan's brother who had made his own escape two years prior. At first Dublin is a colorful kaleidoscope of wonder and mystery, but as the night wears on, the city takes on a darker character, and the two must rely on the kindness of strangers and Bob Dylan's wisdom to persevere. After that night on the streets of inner-city Dublin, the children's dreams have dissolved and they decide to return home, but only after swearing eternal friendship.